2017
DOI: 10.1186/s12877-017-0485-5
|View full text |Cite
|
Sign up to set email alerts
|

Trajectories of Life Satisfaction and their Predictors among Korean Older Adults

Abstract: BackgroundAmong older adults, life satisfaction (LS) correlates with health, mortality, and successful ageing. As various potential threats to LS tend to increase with advancing years, patterns of age-related changes in LS among older adults remain inconsistent. This study aimed to identify LS trajectories in older adults and the characteristics of individuals who experience them.MethodsLarge-scale, nationally representative, longitudinal data collected from 2005 to 2013 were analyzed for this study. The outco… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4
1

Citation Types

6
28
0
7

Year Published

2017
2017
2024
2024

Publication Types

Select...
8
1

Relationship

0
9

Authors

Journals

citations
Cited by 42 publications
(42 citation statements)
references
References 49 publications
6
28
0
7
Order By: Relevance
“…For instance, whereas some study that investigated life satisfaction in adulthood and late life reported that it peaked at age 65 [11], other reported just the inverse with a minimum at age 60 [12]. Results from longitudinal observations of life satisfaction in older population are further confusing as they report improvement [13], deterioration [14,15], or stability over time [16,17]. A terminal decline in life satisfaction has also been described four years before death [18].…”
Section: Introductionmentioning
confidence: 99%
“…For instance, whereas some study that investigated life satisfaction in adulthood and late life reported that it peaked at age 65 [11], other reported just the inverse with a minimum at age 60 [12]. Results from longitudinal observations of life satisfaction in older population are further confusing as they report improvement [13], deterioration [14,15], or stability over time [16,17]. A terminal decline in life satisfaction has also been described four years before death [18].…”
Section: Introductionmentioning
confidence: 99%
“…Depression is one of the most prevalent mental health problems and is associated with general health and quality of life, specifically in late adulthood [ 1 3 ]. Most older adults seem to be exposed to a high risk of depression because they experience a series of losses, such as the death of significant others, retirement, or health problems [ 4 6 ]. Bereavement of a loved one results in social isolation and loneliness, which are significant risk factors for poor mental health and low quality of life [ 7 , 8 ].…”
Section: Introductionmentioning
confidence: 99%
“…As worldwide life expectancy increases, the issue of maintaining wellbeing at an advanced age is growing in importance, as evidence suggests that active engagement with life and positive wellbeing are protective factors for health as people age [ 1 , 2 , 3 , 4 ]. Studies of older people show that subjective wellbeing, in terms of life satisfaction, is affected by the individuals’ state of physical health [ 5 ], socioeconomic status, as well as social and family relationships [ 6 ]; nevertheless, neighborhood environments may also affect the wellbeing of older adults.…”
Section: Introductionmentioning
confidence: 99%